Spectroscopic and Theoretical Study of Cu(I) Binding to His111 in the Human Prion Protein Fragment 106–115 - Arcos-López, Trinidad (Inorg Chem, 2016)
[Image: see text] The ability of the cellular prion protein (PrP(C)) to bind copper in vivo points to a physiological role for PrP(C) in copper transport. Six copper binding sites have been identified in the nonstructured N-terminal region of human PrP(C). Among these sites, the His111 site is unique in that it contains a MKHM motif that would confer interesting Cu(I) and Cu(II) binding properties. We have evaluated Cu(I) coordination to the PrP(106–115) fragment of the human PrP protein, using NMR and X-ray absorption spectroscopies and electronic structure calculations. We find that Met109 and Met112 play an important role in anchoring this metal ion. Cu(I) coordination to His111 is pH-dependent: at pH >8, 2N1O1S species are formed with one Met ligand; in the range of pH 5–8, both methionine (Met) residues bind to Cu(I), forming a 1N1O2S species, where N is from His111 and O is from a backbone carbonyl or a water molecule; at pH <5, only the two Met residues remain coordinated. Thus, even upon drastic changes in the chemical environment, such as those occurring during endocytosis of PrP(C) (decreased pH and a reducing potential), the two Met residues in the MKHM motif enable PrP(C) to maintain the bound Cu(I) ions, consistent with a copper transport function for this protein. We also find that the physiologically relevant Cu(I)-1N1O2S species activates dioxygen via an inner-sphere mechanism, likely involving the formation of a copper(II) superoxide complex. In this process, the Met residues are partially oxidized to sulfoxide; this ability to scavenge superoxide may play a role in the proposed antioxidant properties of PrP(C). This study provides further insight into the Cu(I) coordination properties of His111 in human PrP(C) and the molecular mechanism of oxygen activation by this site.